OA03.03. A clinical study on effect of yoni prakshalan with pancha valkal kwatha in the management of kaphaja yonivapada w.s.r. to candida albicans. - Bhattar, Prabhavati (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: Ayurved has elaborated Gynecological disorders under the entity of yoni vapadas. Kaphaj yoni vapat is one among the twenty yonivapadas, which shoes the symptoms of picchila yonisrava along with yoni kandu. All females of reproductive age group are prone for kaphaj yoni vapat at some time or other and is important Gynecological disorders now a days, in spite of several researches done and plenty of medicines in various forms being available now a days. Pancha valkal kawatha is used for stanika chikitsa(yoni prakshalan), these drug having the qualities of stambhana,kashay rasa, sotha hara and kapha shama beneficial for yonirogas. In this clinical study pancha valkal kwatha has shown significant improvement in white discharge, itching and backache. METHOD: Research conducted on 10 patients from IPD & OPD of Prasuti Tantra & Stree Roga of SDM College of Ayurveda, Hassan. The selection was done on the basis of chief complaints of Kaphaj yonivyapat such as vaginal discharge, itching associated with backache and presence of Candida albicans was proved by vaginal smear. Sthanik chikitsa with Panch valkal kwatha was given for duration of 7 days and patients were asked to maintain local hygiene. Follow up was for 1 week. RESULT: Out of 10 patients, 6 patients were totally cured from the symptoms and mild improvement was observed in the remaining 4 patients at the end of treatment. CONCLUSION: The drug Pancha valkal kawatha is kapha shamaka, stambhaka and having the properties like astringent, antiseptic (kashaya rasa) and wound healing (vrana ropana). Because of these properties it helps in increasing local cell immunity and prevent recurrence of symptoms in patients.